Evaluation of Anti-hyperglycemic Effects of Sodom Apple (Calotropis Procera) Leaf in Diabetes Patients at General Hospital, Azare, Bauchi State, Nigeria (Gadau Journal of Pure and Allied Sciences, 2024)
Diabetes mellitus is a chronic metabolic disorder with increasing prevalence in Nigeria, traditional medicine, including Sodom apple (Calotropis procera) leaf, has been explored as an alternative treatment. This study was carried out at General Hospital, Azare, Bauchi State, Nigeria and Bioscience laboratory of Sa’adu Zungur University Bauchi State to see the anti-hypoglycemic effect of Sodom Apple leaf (Colotropis procera) and phytochemical screening of the leaf. The leaves sample of the plant was collected from Botanical garden of Sa’adu Zungur University Bauchi State. The phytochemical screening revealed and quantified the presence of phenolic compounds and flavonoids in a percentage of 29.1 and 2.8%, respectively. The leaves of Colotropis procera with length 13.5cm long was placed under the feet covered with soaks to generate heat for it to release the active compound for 8hrs per day up to 3days. Fasted blood sugar level test was conducted to see the effectiveness of the leaves at the 3rd day. Methanol and aqueous extracts were found to be highly effective in extracting a wide range of phytochemicals, including alkaloids, saponins, flavonoids, steroids, and terpenoids, with aqueous extracts offering a more diverse profile. Ethanol extracts selectively extracted specific compounds, such as steroids and terpenoids, albeit in smaller quantities. Phytochemical analysis revealed reducing sugars, phenols, and flavonoids, which contribute to the antioxidant properties of the extracts. In diabetic patients, treatment with C. procera leaf extracts significantly reduced fasting blood glucose levels across three groups, with Group 1 showing the most pronounced reduction (from 28.6 mmol/L to 10.0 mmol/L). Groups 2 and 3 also exhibited substantial decreases (from 27.3mmol/L to 12.0mmol/L and from 27.6 mmol/L to 11.6 mmol/L, respectively). These effects could be attributed to the bioactive compounds' abilities to enhance insulin secretion, improve glucose utilization, protect pancreatic β-cells from oxidative stress, and reduce inflammation.  The findings suggest that C. procera leaf extract is a promising candidate for diabetes management due to its efficacy, affordability, and minimal side effects.
Keywords: Colotropis procera; anti-hypoglycemic effect; phytochemical screening